Individual and Social Self-Perception Determinants Among School Going Adolescents - Pidbutska, N. V.; Knysh, A. Ye.; Kvasnyk, O. V.; Shapolova, Victoriia (Wydawnictwo Adam Marszałek, 2021)
The aim of the research is to define individual psychological traits of adolescents that influence the formation of their self-perception. An empirical study was conducted on the basis of general education schools, boarding schools for the hearing impaired students and orphanages of the Kharkiv region (Ukraine). The study included 86 children. In accordance with this aim empirical methods were applied: Self-perception profile for adolescents (SPPA), Freiburg Multifactorial Personality Questionnaire (FPI), An Adolescent’s Character Traits Questionnaire, Rosenberg Self-Esteem Scale. It has been found that self-perception of general education school students is determined by depressiveness, shyness, extroversion, and stuck type of accentuation; in adolescents with hearing impairments – friendliness, reactive aggressiveness, extroversion, emotive and anxiety types of accentuation; in orphans – pedantic and dysthymic types of character accentuation.
Keywords: adolescence; children with limited abilities; individual-and-character traits; orphans; self-consciousness; self-perception; social environment